Fate of Certain Pesticides in Presence of Biochar in Cultivated Soil - EL-Masry, G. N.; Tiilikkala, K. (International Journal of Agricultural Technology, 2018)
Biochar from date palm by product was produced through slow pyrolysis at 450℃ done in a batch retort. The identification of the chemical composition of biochar by using Fourier Transform Infrared spectroscopy, (FTIR) and elemental analysis show that there are function group found around the biochar structure. Its physical characterization by using X-Ray Diffraction (XRD). Surface area (BET analyse) found to be 96.4 m2/gm and its Particle Size Distribution (DLS) had mean size of 172.5 nm and 41.4 nm width. Biochar-amended soil were prepared by thoroughly mixing the soil with accurately weighed of biochar of percentages of 0, 10 and 25 % (w/w). Onion was plant in a sand soil. Two pesticides (Acetamprid and Oxamyl) were applied once after 60 days from planting. Residues were extracted inside onion blubs after 1, 3, 7 and 14 days from application. It is clearly proved that the half-life time of both pesticides are increased in the soil contain biochar. In addition to the leaching of pesticides from the agricultural soils to the run out water show statistically significant as the soil contain biochar had no pesticide residues after application.